Fluorine in shallow groundwater in China: A review of distribution, occurrence and environmental effects - Zhao, Ping; Zhang, Shuheng; Xu, Kaijian; Zhao, Yuejiao; Shen, Pengju; Zhu, Lele; Zheng, Liugen (Frontiers in Earth Science, 2023)
With rapid economic development and the increasing demand for drinking water, a large amount of groundwater is exploited, resulting in a high F- content in groundwater, which is harmful to the environment and human body. In this study, 5464 data points of fluoride in shallow groundwater were collected, and the F- content distribution, occurrence form and environmental impact of shallow groundwater were discussed. The results showed that (1) the F- content in shallow groundwater in China ranged from 0 to 60 mg/L, with a mean content of 0.90 mg/L; the lowest average F- content in shallow groundwater in Southwest China was 0.36 mg/L; South China (1.20 mg/L), Northeast China (1.25 mg/L) and Northwest China (1.25 mg/L) were considered high-fluoride areas, and North China (0.93 mg/L), East China (0.67 mg/L) and Central China (0.80 mg/L) were considered low-fluoride areas. The mean F- content in groundwater differed between provinces and cities. (2) The F- in shallow groundwater mainly occurred in ionic, complex ionic and organic fluoride molecular states. (3) The influence of a high F- content in shallow groundwater on the environment was mainly manifested in the increase in water F- concentration and soil F- and vegetable F- content. The influence of a high F- content on the human body was mainly manifested in an increase in urinary F- content in children, a high prevalence of dental fluorosis in children, an increase in skeletal fluorosis rate in adults with age, and an influence on cognitive function of older adults. These results provide a basis for F- pollution control and high-fluoride water treatment.